ANALISIS EFEKTIVITAS PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA PEMBELAJARAN IPAS - Dyah Ratnasari; Sulianto, Joko; Noer, Hamidah (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2025)
This study aims to evaluate the efficacy of teaching methodology at the Right Level (TaRL) in improving student learning outcomes in the subjects of Natural Sciences and Social Sciences (IPAS) Class III. This study used a pretest-posttest design of one group with 28 students from Sdn Sawah Besar 01 Semarang. Quantitative Data from pre-test and post-test analyses were evaluated using paired t-tests, revealing significant differences in student learning outcomes before and after the application of TaRL strategies (p < 0.05). The post-test average value increased from 60.36 to 81.79, and the N-Gain calculation showed an average value of 0.625, which belongs to the category of medium increase. Furthermore, qualitative data collected from interviews with educators and students, along with observations in the classroom, show that the TaRL method increases student engagement, facilitates more adaptable learning based on individual abilities, and creates a dynamic and inclusive learning atmosphere. Although the results are quite positive, there is still room for improvement in the application of this method in order to achieve more optimal results. Research shows that TaRL strategies effectively improve student learning outcomes, with the potential for additional adjustments to meet individual student needs.